2019
DOI: 10.1371/journal.pone.0223181
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile changings after switching from rilpivirine/tenofovir disoproxil fumarate/emtricitabine to rilpivirine/tenofovir alafenamide/emtricitabine: Different effects in patients with or without baseline hypercholesterolemia

Abstract: Tenofovir alafenamide (TAF) has similar efficacy compared to tenofovir disoproxil fumarate (TDF), but a less favorable effect on lipids. Aim of this retrospective multicentre study was to evaluate the impact on lipids of switching from rilpivirine (RPV)/ emtricitabine (FTC)/TDF to RPV/FTC/TAF in a cohort of HIV-1 infected patients. Total cholesterol (TC), high density lipoproteins (HDL) and low density lipoproteins (LDL) were compared at the moment of the switch and at the first following evaluation, by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 17 publications
5
18
1
Order By: Relevance
“…Previous studies have also shown the elevation in the LDL-C and TG levels, but the range of elevation depended on the observational period, and the characteristics of the participants (17)(18)(19). One of the major risks for hyperlipidemia that was identi ed after switching to TAF was the elevation at beginning in TG or LDL-C levels (20) although opposite results also reported (21). In our study, LDL-C levels increased regardless of the hyperlipidemia at baseline.…”
Section: Discussioncontrasting
confidence: 52%
“…Previous studies have also shown the elevation in the LDL-C and TG levels, but the range of elevation depended on the observational period, and the characteristics of the participants (17)(18)(19). One of the major risks for hyperlipidemia that was identi ed after switching to TAF was the elevation at beginning in TG or LDL-C levels (20) although opposite results also reported (21). In our study, LDL-C levels increased regardless of the hyperlipidemia at baseline.…”
Section: Discussioncontrasting
confidence: 52%
“…RPV should be taken with a normal caloric meal (533 Kcal) or high-fat high-caloric meal (928 Kcal) and need careful evaluation of possible drug interactions, in particular with proton pump inhibitors and antiepileptic drugs. In a trial on healthy volunteers that were exposed to intravenous nanosuspension, maximum concentration was achieved in three days and decreased to below 10 ng/mL after 12–26 weeks with a half-life of five weeks [ 19 , 20 , 21 ].…”
Section: Rilpivirine (Rpv; Tmc278) Long Acting (Rpv-la)mentioning
confidence: 99%
“…While switch-over from TDF to TAF may be associated with an improvement in bone and renal safety in HBV-infected patients, changes in lipid profile have also been noted with TDF to TAF switch-over in people living with HIV. A significant increase in total and low-density lipoprotein cholesterol and decrease in high-density lipoprotein cholesterol has been noted with switch-over from TDF- to TAF-based regimen in HIV-infected individuals [ 72 74 ]. However, these results have not been confirmed in HIV-infected individuals with baseline hypercholesterolemia [ 72 ].…”
Section: Tenofovir Alafenamide: a Safer Alternative To Tdfmentioning
confidence: 99%
“…A significant increase in total and low-density lipoprotein cholesterol and decrease in high-density lipoprotein cholesterol has been noted with switch-over from TDF- to TAF-based regimen in HIV-infected individuals [ 72 74 ]. However, these results have not been confirmed in HIV-infected individuals with baseline hypercholesterolemia [ 72 ]. The clinical relevance of these findings, if any to HBV-infected individuals, remains to be established.…”
Section: Tenofovir Alafenamide: a Safer Alternative To Tdfmentioning
confidence: 99%